Strengthening Banana Chips MSME Empowerment through Appropriate Production Technologies and Digital Bookkeeping in Pamijahan Village - Andi Hidayat Muhmin; Gilang Pratama Hafiz; Ritta Setiyati (KENDURI : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
This community service program aimed to strengthen the empowerment capacity of banana chips micro, small, and medium enterprises (MSMEs) through appropriate production technologies and digital bookkeeping in Pamijahan Village, Bogor Regency, West Java, Indonesia. The program was implemented from June to October 2025 and involved 19 women MSME actors who were members of a local PKK-based banana chips business group. A participatory and practice-based approach was applied through five stages: needs assessment, training, technology implementation, mentoring, and evaluation. The production intervention included hygienic production training, the use of a banana slicing machine, an oil spinner, and hygiene equipment. The business management intervention focused on digital bookkeeping, cash-flow understanding, simple financial recording, and business planning assistance. The evaluation used descriptive indicators to compare partner conditions before and after the program. The results showed improvements in production efficiency, product consistency, hygienic practices, appropriate technology use, digital bookkeeping adoption, cash-flow understanding, and simple business planning. Production efficiency, based on observed reductions in slicing and oil-reduction time supported by partner reports, increased by up to 30%. In addition, all participants used hygiene equipment during production practice, and 15 out of 19 participants, or approximately 79%, began recording income and expenses using a simple digital bookkeeping application. The program indicates that the integration of appropriate production technologies and digital bookkeeping can serve as a practical empowerment model for women-led food-based MSMEs in rural communities.